MEWAR: Development of a Cross-Platform Mobile Application and Web Dashboard System for Real-Time Mosquito Surveillance in Northeast Brazil - Aldosery, Aisha; Musah, Anwar; Birjovanu, Georgiana; Moreno, Giselle; Boscor, Andrei; Dutra, Livia; Santos, George; Nunes, Vania; Oliveira, Rossandra; Ambrizzi, Tercio; Massoni, Tiago; dos Santos, Wellington Pinheiro; et al. (Frontiers in Public Health, 2021)
Mosquito surveillance is considered one of the best-established and most effective health intervention programs for controlling and preventing the spread of mosquito-borne diseases. Environmental surveillance agents who perform the routine entomological surveys of properties in areas where mosquito-borne diseases are endemic are playing a crucial role in vector surveillance by finding and destroying mosquito hotspots and reporting data collected on the locations of the vectors. At the moment, this involves the time-consuming process of recording information on paper-based forms. The introduction of mobile surveillance applications will therefore improve the process of data collection, data reporting, and field worker performance. Digital-based surveillance is also critical in being able to report real-time data, as opposed to the current approach, which relies largely on manual reporting after data entry using paper forms. Finally, real-time data capturing could also be used for predictive analytical models to predict mosquito population dynamics and to enable early warning of hotspots to direct the fieldwork of surveillance agents. This paper describes the development of a cross-platform digital MEWAR surveillance system for improving mosquito surveillance in Brazil. The system comprises two components: a dashboard for managers and a mobile application for health agents. The dashboard enables managers to assign properties to health workers who then survey them for mosquitoes and to monitor the progress of inspection visits in real time. The mobile application, which was primarily designed as a data collection tool, enables the environmental surveillance agents to act on their assigned tasks and to record the details of the property inspections by filling out digital forms built into the mobile application rather than paper-based forms. The application records mosquito infestation. The system presented here is a real-world use case that has been co-authored and developed in collaboration with environmental agents in two Brazilian cities where it is currently being piloted.